Reasons and Sources of Hesitancy Against COVID-19 Vaccine: A Cross-Sectional Study among General Public in Pakistan - Ali Usman, Areeba Arshad Qureshi, Areeha Munawar, Areeba Mujeeb, Humna Naseer, Tahreem Fatima, Mohammad Amin Qadeemi, Sohail Arshad, Hekmatullah Nursi, Romail Haider, Muhammad Sohaib (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction:Since Coronavirus Disease-2019 (COVID-19) is a respiratory infection which is transmitted by respiratory droplets, it has now spread all across the globe. There are various myths and misconceptions about this vaccination that act as a prime barrier to vaccinate majority of the population. Methods: A cross-sectional-study was performed from all over Punjab province using convenience sampling technique. A sample size of 400 was gathered in this study by o digital and hardcopy questionnaires after the participants gave their consent. Results: The willingness to vaccinate against COVID-19, was only 28.0% while the greater remainder of 72% opted for ‘no’ or ‘maybe’. Our study prevailed that the most common reason of hesitancy among the population was that vaccine can cause blood to clot and people may die (15.6%). And the most frequent source emerged to be social media by 23%. Discussion: The study revealed that people with no or low educational status were more uncertain or hesitant towards vaccine administration as well as those belonging to ages 41-50 years.